Study of egg traits among improved varieties of chicken reared under backyard poultry production system - MADDHESHIYA, P K; ALI, NAZIM; FAHIM, AHMAD; BHARTI, M K; SINGH, RAJBIR; ROY, DEBASHIS; SAHU, D S (The Indian Journal of Animal Sciences, 2020)
The aim of the study was to evaluate the egg traits among improved varieties of chicken reared under backyard poultry production system. The results indicated superiority of rearing these improved varieties under backyard production system in terms of their external and internal egg traits. Significant differences were observed in egg weight, shape index and shell weight of eggs which was superior in CARI-Devendra birds followed by CARISonali and CARI-Hitkari. The yolk weight in different varieties of chicken differ significantly. However, no difference in albumin weight was observed in the study. The egg indices and haugh unit was also superior in CARI-Devendra than other varieties of chicken. Further, it was found that management and its interaction had significant effect on egg weight and yolk colour in few varieties. Thus, it may be suggested that egg traits differ in different improved varieties of chicken and CARI Devendra and CARI Sonali may be promoted under backyard production system according to the demand for brown and white eggs, respectively.